Synthesis, H2S releasing properties, antiviral and antioxidant activities and acute cardiac effects of nucleoside 5′-dithioacetates - Miklós Bege; Miklós Lovas; Dániel Priksz; Brigitta Bernát; Ilona Bereczki; Rasha Ghanem Kattoub; Richárd Kajtár; Simon Eskeif; Levente Novák; Jan Hodek; Jan Weber; Pál Herczegh; et al. (Scientific Reports)
Abstract Hydrogen sulfide (H2S) is an endogenous gasotransmitter with cardioprotective and antiviral effects. In this work, new cysteine-selective nucleoside-H2S-donor hybrid molecules were prepared by conjugating nucleoside biomolecules with a thiol-activatable dithioacetyl group. 5′-Dithioacetate derivatives were synthesized from the canonical nucleosides (uridine, adenosine, cytidine, guanosine and thymidine), and the putative 5′-thio metabolites were also produced from uridine and adenosine. According to our measurements made with an H2S-specific sensor, nucleoside dithioacetates are moderately fast H2S donors, the guanosine derivative showed the fastest kinetics and the adenosine derivative the slowest. The antioxidant activity of 5′-thionucleosides is significantly higher than that of trolox, but lower than that of ascorbic acid, while intact dithioacetates have no remarkable antioxidant effect. In human Calu cells, the guanosine derivative showed a moderate anti-SARS-CoV-2 effect which was also confirmed by virus yield reduction assay. Dithioacetyl-adenosine and its metabolite showed similar acute cardiac effects as adenosine, however, it is noteworthy that both 5′-thio modified adenosines increased left ventricular ejection fraction or stroke volume, which was not observed with native adenosine.